Diarylheptanoid 7-(3,4-Dihydroxyphenyl)-5- Hydroxy-1-Phenyl- (1E)-1-Heptene from Curcuma Comosa Roxb. Inhibits Nucleophosmin Localization and Induces Apoptosis in KG-1a Leukemic Stem Cells - Viriyaadhammaa, Natsima; Duangmano, Suwit; Panyajai, Pawaret; Gyi, Khin Khin; Tima, Singkome; Chiampanichayakul, Sawitree; Okonogi, Siriporn; Dejkriengkraikul, Pornngarm; Krise, Jeffrey; Saiai, Aroonchai; Anuchapreeda, Songyot (Journal of Health Science and Medical Research, 2024)
Objective: This study aimed to investigate the effect of the diarylheptanoid 7-(3,4-dihydroxyphenyl)-5- hydroxy-1-phenyl-(1E)-1-heptene (DDHPH) from the rhizome of Curcuma comosa Roxb. on nucleophosmin (NPM) protein localization followed by induced cell death in KG-1a leukemic stem cells. Material and Methods: DDHPH was purified by column chromatography and characterized by nuclear magnetic resonance (NMR). Localization of NPM was determined by a confocal microscopy. Induction of cell death was determined by flow cytometry and Western blotting. Results: A previous study showed that NPM directly interacted with p53 and activates p53 function. In this study, DDHPH was found to modify the translocation of NPM and enhance both p53 and cleaved caspase-3 expression. These proteins were found to control cell cycle progression and cell apoptosis induction. Conclusion: This study demonstrated that DDHPH is a novel compound which induces cell death through NPM localization.